2020
DOI: 10.1073/pnas.2012999117
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of ligand-induced allosteric transitions in a PDZ domain

Abstract: While allostery is of paramount importance for protein regulation, the underlying dynamical process of ligand (un)binding at one site, resulting time evolution of the protein structure, and change of the binding affinity at a remote site are not well understood. Here the ligand-induced conformational transition in a widely studied model system of allostery, the PDZ2 domain, is investigated by transient infrared spectroscopy accompanied by molecular dynamics simulations. To this end, an azobenzene-derived photo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 75 publications
3
63
0
Order By: Relevance
“…In other words, sector residues are only marginally coupled to the rest of the structure, a feature that is likely driven by the requirement of dynamics to function, and in this case, to accommodate the ligand. In fact, MD simulations point to the ligand binding regions (all of which form a part of the sector) exhibiting large dynamics in the native ensemble ( Bozovic et al., 2020 ; Kumawat and Chakrabarty, 2020 ) consistent with our observations of marginal coupling. A similar observation can also be made in the enzyme dihydrofolate reductase (DHFR) where the strongly coupled residues constitute one face of the protein acting as a base while the marginally coupled residues are involved in ligand-cofactor binding and catalysis ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…In other words, sector residues are only marginally coupled to the rest of the structure, a feature that is likely driven by the requirement of dynamics to function, and in this case, to accommodate the ligand. In fact, MD simulations point to the ligand binding regions (all of which form a part of the sector) exhibiting large dynamics in the native ensemble ( Bozovic et al., 2020 ; Kumawat and Chakrabarty, 2020 ) consistent with our observations of marginal coupling. A similar observation can also be made in the enzyme dihydrofolate reductase (DHFR) where the strongly coupled residues constitute one face of the protein acting as a base while the marginally coupled residues are involved in ligand-cofactor binding and catalysis ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…Such a mechanism, in which the binding of ligands causes a partial shift in protein state population, but does not completely depopulate states, has been shown before for other systems. 5,33 This mechanism would best explain our data, but has to be further investigated. A recent study on yeast Hsp90 also found two fast interconverting closed states.…”
Section: Resultsmentioning
confidence: 86%
“…Capturing the time evolution of the allosteric activation of enzymes toward the formation of the ternary complex involves deciphering the interplay of fast and slow conformational dynamics coupled to effector and substrate binding. (11) The transient nature of the ternary complex and the allosteric transition of enzymes undergoing turnover hampers the structural and dynamic characterization of allosteric mechanisms and the identification of functionally relevant states. (12)(13)(14)(15)(16)(17) It is therefore not surprising that the allosterically active state remains hidden for several enzymes.…”
Section: Introductionmentioning
confidence: 99%